Abnormal Right Ventricular Myocardial Performance Index Is Not Associated With Outcomes in Invasively Ventilated Intensive Care Unit Patients Without Acute Respiratory Distress Syndrome—Post hoc Analysis of Two RCTs - Pierrakos, Charalampos; Geke Algera, Anna; Simonis, Fabienne; Cherpanath, Thomas G. V.; Lagrand, Wim K.; Paulus, Frederique; Bos, Lieuwe D. J.; Schultz, Marcus J.; , the PReVENT– and RELAx–Investigators (Frontiers in Cardiovascular Medicine, 2022)
Background The objective of the study was to determine the association between right ventricular (RV) myocardial performance index (MPI) and successful liberation from the ventilator and death within 28 days. Methods Post hoc analysis of 2 ventilation studies in invasively ventilated patients not having ARDS. RV-MPI was collected through transthoracic echocardiography within 24–48 h from the start of invasive ventilation according to the study protocols. RV-MPI ≤ 0.54 was considered normal. The primary endpoint was successful liberation from the ventilator < 28 days; the secondary endpoint was 28-day mortality. Results A total of 81 patients underwent transthoracic echocardiography at median 30 (24–42) h after the start of ventilation—in 73 (90%) patients, the RV-MPI could be collected. A total of 56 (77%) patients were successfully liberated from the ventilator < 28 days; A total of 22 (30%) patients had died before or at day 28. A total of 18 (25%) patients had an abnormal RV-MPI. RV-MPI was neither associated with successful liberation from the ventilator within 28 days [HR, 2.2 (95% CI 0.47–10.6); p = 0.31] nor with 28-day mortality [HR, 1.56 (95% CI 0.07–34.27); p = 0.7]. Conclusion In invasively ventilated critically ill patients without ARDS, an abnormal RV-MPI indicative of RV dysfunction was not associated with time to liberation from invasive ventilation.